2014
DOI: 10.1155/2014/476207
|View full text |Cite
|
Sign up to set email alerts
|

Yarrowia lipolyticaand Its Multiple Applications in the Biotechnological Industry

Abstract: Yarrowia lipolytica is a nonpathogenic dimorphic aerobic yeast that stands out due to its ability to grow in hydrophobic environments. This property allowed this yeast to develop an ability to metabolize triglycerides and fatty acids as carbon sources. This feature enables using this species in the bioremediation of environments contaminated with oil spill. In addition, Y. lipolytica has been calling the interest of researchers due to its huge biotechnological potential, associated with the production of sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(79 citation statements)
references
References 93 publications
(206 reference statements)
0
65
0
1
Order By: Relevance
“…The metabolism of glycerol to citric acid [42] and lipogenesis pathway [43] in Y. lipolytica has been studied before. Glycerol is assimilated into the cell via facilitated diffusion and is subsequently phosphorylated [41].…”
Section: Discussionmentioning
confidence: 99%
“…The metabolism of glycerol to citric acid [42] and lipogenesis pathway [43] in Y. lipolytica has been studied before. Glycerol is assimilated into the cell via facilitated diffusion and is subsequently phosphorylated [41].…”
Section: Discussionmentioning
confidence: 99%
“…Y. lipolytica is a yeast often isolated from hydrophobic substrates, rich in alkanes and fats, for example, cheese, yoghurt, soy sauce, meat, and shrimp salad, and is used in many industrial processes to obtain various products, such as citric and isocitric acids, γ-decalactone, lipase, and for its ability to produce and store lipids (Gonçalves, Colen, & Takahashi, 2014). Furthermore, it has been demonstrated that some Y. lipolytica strains are able to reduce pollution in olive mill wastewaters (Gonçalves, Lopes, Ferreira, & Belo, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, genus Yarrowia, which contains a single-species Yarrowia lipolytica was present in high numbers in one of the samples. The species has attracted a lot of interest because of its very high biotechnological potential, especially due to its lipid metabolism abilities (Gonçalves et al, 2014), which are likely also useful for survival in the ecosystem of the dishwasher.…”
Section: Discussionmentioning
confidence: 99%